Development of a process model for remote agent call center the case of Convergys - Madriaga, John Voltaire C.; Rañeses, Nestor O. (Quezon City University of the Philippines Diliman, 2006)
This project explores the options that have been made available through development of advanced technologies in broadband communications and the internet. What started off as a contingency plan or disaster recovery option can be used to extend traditional and conventional workplace environment into our homes. It also gives the possibility for mothers, students, government employees or members from the academe to get extra income. Much of the technology and the hardware requirements are already in place. The company's servers have excess capacity and the technological capacity to support Work from Home Setup or a Remote Agent Call Center. The project, if implemented will also be able to help address challenges being encountered by the company in hiring new agents, retaining agents or attrition, and the ever growing need for agent workstations. This is not a silver bullet solution, but an option that can be explored. For the purpose of this academic exercise, the parameters have been limited to the recommendation stage. Certain figures have also been provided, however they are not exact or only ballpark figures since actual figures have been deemed proprietary and confidential. The proponent however assures that even with estimate figures, the reader will have a firm grasp of the goals, objectives, and benefits of the project. It can also be said, that at the time of submission of this paper, the actual Continuous Improvement Initiative entitled "Remote Agent Call Center" has been submitted to Convergys' CI portal awaiting reviews and feedback. Should a go signal be given by stakeholders and upper management to implement the process, proponent will take the lead in transitioning the project to the Implementations Department. As much as possible, simple solutions and readily available tools were selected. At the remote agent's side, all that is really needed in terms of equipment and tools may already be present. Certainly, a bigger percentage of households in the country already have desktop computers or personal computers. Major Telephone providers now have DSL and broadband connection available in Metro Manila, and outlying provinces. Current prices for broadband residential connections with IP address has also gone down significantly. It is also hoped that readers will be given a glimpse of the call center industry and some of the challenges. After reading the paper, it will also provide awareness of VoIP and the technologies that can be used by anyone with broadband internet connection.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Convergys Corporation; Broadband communication systems; Technological innovations